IMPROVING REGIONAL ORIGINAL INCOME WITH TAX RECEIPT, REGIONAL RETRIBUTION AND REGIONAL WEALTH MANAGEMENT RESULTS IN SOLO RAYA - Suprihati Suprihati; LMS Kristiyanti; M. Hajir (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study uses secondary data, which comes from the realization of District / City Regional Revenues in the Surakarta Residency 2012-2016 Fiscal Year. The data analysis using multiple linear regression analysis with the help of SPSS 20. The results of the study indicate that tax revenue has a significant effect on the Original Revenue of District / City Regions in the Surakarta Residency. Whereas the regional retribution does not have a significant effect on the Original Revenue of District / City Regions in the Surakarta Residency. Regional wealth management has a significant effect on the District / City Regional Original Revenue in the Residency. Tax revenues, regional retributions and management of regional wealth together influence the Original Revenue of District / City Regions in the Surakarta Residency. The calculation results show that tax revenue has a value of beta coefficient of 0.442 which is greater than the variable regional levies and regional wealth management. This shows that tax revenue is more dominant in influencing the Original District / City Revenue in the Surakarta Residency. Keywords : tax revenue, regional retribution, management of regional wealth, local revenue.